RANCANG BANGUN SISTEM ADMINISTRASI SURAT KETERANGAN DAN KEPENDUDUKAN BERBASIS WEBSITE MENGGUNAKAN ALGORITMA BOYER MOORE - M Wildan Kafafi; I Kadek Dwi Nuryana; Muhammad Fatkhur Rizal (Inovate, 2025)
Every year the population of Sukomulyo village will increase so that the tasks and burdens of the Sukomulyo village government will also increase along with the increasing population, to overcome this the village government must be able to work optimally such as providing administrative services using an administration system so that services can be carried out quickly and efficiently. And with the existence of a village administration system, it can help the village government in managing population data that can be done independently so that it becomes information for village development and construction. to maximize system performance when searching for population data and letter data, researchers want to use a string search algorithm, namely the Boyer Moore algorithm, the Boyer Moore algorithm is one of the string search algorithms that is able to produce very good search performance because it has a large character matching jump. Based on the results of testing carried out from several stages of testing, the first test was carried out by entering a pattern with several input patterns that were searched for, the fastest search time was obtained, namely 363 milliseconds, in the second test carried out by classifying data based on the amount of data in the database, the results showed that the amount of data in the database did not greatly affect the performance of the Boyer Moore algorithm when searching. So, from several stages of testing that were carried out, it was proven that using the Boyer Moore algorithm provides fast and efficient data search performance. Keywords: village administration system, Boyer Moore algorithm, thesis topic.